2015
DOI: 10.1007/s10900-015-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Caregivers of Young Children: Oral Health Beliefs, Attitudes, and Early Childhood Caries Knowledge

Abstract: The incidence of early childhood caries (ECC) is a global public health concern. The oral health knowledge of a caregiver can affect a child's risk for developing ECC. An exploratory study of the oral health knowledge and behaviors among caregivers of children 6 years of age and younger was conducted with a convenience sample of adults (n = 114) enrolled in English language or high school equivalency examination courses. The majority of study participants were born in Asia (47 %). Other birth regions included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…If there is, the cost is quite high which is not affordable for parents who have low income. Therefore, they prefer the closest public or private dentist but not the cheapest as they still want to give the best and quick treatment to their children [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…If there is, the cost is quite high which is not affordable for parents who have low income. Therefore, they prefer the closest public or private dentist but not the cheapest as they still want to give the best and quick treatment to their children [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Tal sugere que existe menor investimento na escovagem durante o período de dentição decídua, o que poderá estar associado à menor importância que lhe é associada pelos cuidadores, [31][32][33] nomeadamente nos estabelecimentos de ensino pré -escolar, onde existem oportunidades para introduzir hábitos regulares e sustentáveis de escovagem em crianças de todos os níveis socioeconómicos. 18,34 Nos Estados Unidos da América, 35 114 imigrantes adultos (47% asiáticos), cuidadores de crianças com ≤ 6 anos de idade, revelaram uma correlação significativa entre uma saúde dentária 'pobre' nas crianças e a crença pelos cuidadores de que a escovagem dentária não se devia iniciar com a erupção do primeiro dente.…”
Section: Discussionunclassified
“…Because oral health of the children is closely linked to the circumstances and lifestyle of the child’s caregivers, early intervention programs should include their parents [ 32 , 33 ]. This research is required since little is reported about the state of the currently accessible oral health-related smartphone application in Malaysia, and there are no prior studies available on the overall development and usability of the current mobile application that focuses on both diet and oral health for the prevention of early childhood caries.…”
Section: Introductionmentioning
confidence: 99%